Land degradation in the Oromiya highlands in Ethiopia: Community and household perspectives on the nature, causes and policy implications - Jabbar, M.A.; Ayele, G. (Lambert Academic Publishing, 2011)
Poverty, malnutrition, low agricultural productivity, severe land degradation, shortage of water and fuel wood are common problems in the highlands of Ethiopia. A complex set of natural, political, and socio- economic factors have been responsible for the degradation of land resources. This study was conducted to characterize the nature of land use practices, nature and extent of land degradation in the highlands, assess the causes of land use change and land degradation, identify knowledge gaps and some options about the possible pathways of overcoming the problems and improve agricultural productivity. This study shows that the perspectives of local communities and households about the dynamics of land use, management and the degradation process and possible solutions are very useful and practical contribution to the research, extension and policy making community as well as the generality of citizens in the region.